A State-of-the-Art of Functional Scaffolds for 3D Nervous Tissue Regeneration - Tupone, Maria Grazia; d’Angelo, Michele; Castelli, Vanessa; Catanesi, Mariano; Benedetti, Elisabetta; Cimini, Annamaria (Frontiers in Bioengineering and Biotechnology, 2021)
Exploring and developing multifunctional intelligent biomaterials is crucial to improve next-generation therapies in tissue engineering and regenerative medicine. Recent findings show how distinct characteristics of in situ microenvironment can be mimicked by using different biomaterials. In vivo tissue architecture is characterized by the interconnection between cells and specific components of the extracellular matrix (ECM). Last evidence shows the importance of the structure and composition of the ECM in the development of cellular and molecular techniques, to achieve the best biodegradable and bioactive biomaterial compatible to human physiology. Such biomaterials provide specialized bioactive signals to regulate the surrounding biological habitat, through the progression of wound healing and biomaterial integration. The connection between stem cells and biomaterials stimulate the occurrence of specific modifications in terms of cell properties and fate, influencing then processes such as self-renewal, cell adhesion and differentiation. Recent studies in the field of tissue engineering and regenerative medicine have shown to deal with a broad area of applications, offering the most efficient and suitable strategies to neural repair and regeneration, drawing attention towards the potential use of biomaterials as 3D tools for in vitro neurodevelopment of tissue models, both in physiological and pathological conditions. In this direction, there are several tools supporting cell regeneration, which associate cytokines and other soluble factors delivery through the scaffold, and different approaches considering the features of the biomaterials, for an increased functionalization of the scaffold and for a better promotion of neural proliferation and cells-ECM interplay. In fact, 3D scaffolds need to ensure a progressive and regular delivery of cytokines, growth factors, or biomolecules, and moreover they should serve as a guide and support for injured tissues. It is also possible to create scaffolds with different layers, each one possessing different physical and biochemical aspects, able to provide at the same time organization, support and maintenance of the specific cell phenotype and diversified extracellular matrix morphogenesis. Our review summarizes the most recent advancements in functional materials, which are crucial to achieve the best performance and at the same time, to overcome the current limitations in tissue engineering and nervous tissue regeneration.